Direct Contact with Nature and Online Perspective: Does it Make a Difference in Environmental Attitudes Regarding the Nature Conservation Challenges in Serbia? - Stojanović, Vladimir; Lazić, Lazar; Pantelić, Milana; Obradović Strålman, Sanja; S. Dragin, Aleksandra (Geographica Pannonica, 2024)
Attitudes towards environment are important for organizing nature protection, especially in countries undergoing political and economic transition. In this paper, attitudes of visitors, local communities and stakeholders towards the environment and nature protection are researched online and within the Special Nature Reserve and surroundings settlements. Data were obtained on the basis of the survey research as part of the ’LIFE WILDisland’ project. Additionally, this paper was focused on comparing the attitudes of respondents between those who were in direct contact with nature and those who responded online. Gained results showed that respondents who were in direct contact with nature have more intensive interactions with it and have a good understanding of conservation-restoration measures. Both groups of respondents support nature protection activities.